AI investment in education and training and economic growth in the USA - Dervis Kirikkaleli; Nurdan O. Kirikkaleli (Social Sciences and Humanities Open, 2025)
The present study aims to explore the effect of artificial intelligence (AI) investment in education and training on gross domestic product (GDP) in the United States of America (USA) while controlling for the traditional determinants of labor and capital. In order to achieve this aim, the present study used the Fourier ADL (Autoregressive Distributed Lag) cointegration, Dynamic Ordinary Least Squares (DOLS), and Canonical Cointegrating Regression (CCR) estimators from 2012 to 2022 and used a quarterly dataset. The outcomes of the study reveal that (i) there is long run linkage between GDP, labor force, gross fixed capital formation, and AI investment in education and training in the USA; (ii) rising AI investment in education and training in the USA is associated with increasing GDP; (iii) capital and labor also contributed to the GDP, positively. US policymakers should continue supporting technological investment in education to maintain sustainable investment and growth. Technology companies and universities should collaborate to design AI-driven curricula, while businesses should invest in workforce upskilling. This collaboration will enhance the economic benefits of AI.